?The Fatty Acid Composition of Pithecello- bium dulce Seed Oil (Biological Sciences - PJSIR, 2022)
Shimadzu gas chromatograph fitted with a flame ionisations detector. The identification and percentage composition of the component fatty acids were determined by running a standard mixture of methyl esters, their retention time and peak areas.